Characteristics of TiNx/n-Si Schottky diodes deposited by reactive magnetron sputtering - Dimitriadis, CA; Lee, JI; Patsalas, P; Logothetidis, S; Tassis, DH; Brini, J; Kamarinos, G (AMER INST PHYSICS, 1999)
The effects of the substrate bias voltage and the deposition temperature on the electrical characteristics and the 1/f noise of TiNx/n-Si Schottky diodes fabricated by reactive magnetron sputtering are investigated. As the substrate bias voltage varies from -40 to -100 V, the ideality factor of the diodes remain almost unchanged whereas the noise intensity as a function of the current shows a shift parallel by about one order of magnitude. At low current levels, the noise intensity is proportional to the current and is attributed to the mobility and diffusivity fluctuation. At higher current levels, the noise intensity is proportional to the square of the current and is attributed to bulk traps mainly near the interface. Analysis of the noise measurements shows that both the Hooge parameter and the bulk trap density near the interface first are increased and then decreased as the negative substrate bias voltage increases from 240 to -100 V. This is in contrast with the effects of the deposition temperature where we found that the Hooge parameter remains almost constant, while both the ideality factor and the interface states density are decreased as the deposition temperature increases from room temperature to 400 degrees C. The trap properties of the TiNx/n-Si Schottky diodes are correlated with the stoichiometry of the TiNx films investigated by spectroscopic ellipsometry measurements. (C) 1999 American Institute of Physics. [S0021-8979(99)00808-7].
Keywords: THIN-FILMS; TITANIUM NITRIDE; BARRIER DIODES; 1/F NOISE; IN-SITU; TI-W; SILICON; DEFECTS; CONTACTS; METAL